PERILAKU BULLYING: ASESMEN MULTIDIMENSI DAN INTERVENSI SOSIAL - Yusuf, Husmiati; Fahrudin, Adi (Faculty of Psychology, Diponegoro University, 2012)
This paper presented an overview about bullying, multidimentional assessment, and social intervention. Bullying is an act of repeated aggressive behavior in order to intentionally hurt another person physically or mentally. Bullying is characterized by an individual behaving in a certain way to gain power over another person. Behaviors may include name calling, verbal or written abuse, exclusion from activities, exclusion from social situations, physical abuse, or coercion. Bullying in schools sometimes consists of a group of students taking advantage of, or isolating one student in particular and gaining the loyalty of bystanders who want to avoid becoming the next victim. To comprehensively understand about bullying, professional helpers (psychologist, counsellor, and social worker) need to do a multidimentional assesment. Based on this issue, this paper suggested three intervention programs to prevent and combating the bullying behavior in the schools is Citizens’ Responsibility Program.Keywords: school, bullying, assessment, intervention